SOCIALIZATION OF CEDAR PROGRAM (CEGAH DIARE) IN CHILDREN OF ELEMENTARY SCHOOL X BOGOR CITY - Simanungkalit, Sintha Fransiske; Amar, M. Ikhsan; Hadi, Prasetyo (Jurnal Abdi Insani, 2022)
The prevalence of diarrhea in Indonesia according to the characteristics based on Riskesdas 2018 was recorded for ages <1 year as many as 18,225 children (9%), ages 1 - 4 years as many as 73,188 children (11.5%), ages 5 - 14 years 182,338 (6.2). %), and 165,644 children (6.7%) aged 15 - 24 years (Ministry of Health, 2019). The problem of diarrhea in children often occurs in SDN X Bogor City, this is what underlies the community service team to provide counseling to students at SDN X Bogor City. The purpose of this activity is to increase the knowledge of the students of SDN X Bogor City so that these students can prevent and avoid diarrheal diseases. This activity uses nutrition promotion techniques with counseling and singing songs so that it is easier for children to remember. Prior to this activity, nutrition promotion for elementary school children was asked to fill out an initial questionnaire to determine the level of knowledge related to children after being given nutrition promotion which was measured again the level of children’s knowledge. At the time before the counseling (pre test) the minimum obtained by the child was 2 and the maximum value was 9 and the average value obtained was 5.51. Meanwhile, the minimum post-test score obtained by the children was 3, the maximum was 10 and the average score was 7.39. T Test Dependent Test was carried out to see if there was a difference before and before the extension and the p-value was 0.000. The p-value means that there is a difference in knowledge before and before providing counseling to SDN children. In addition, there is an increase in the knowledge of elementary school children regarding the problem of diarrhea. This outreach activity in the form of nutrition promotion in the form of counseling can effectively increase the knowledge of SDN X students in Bogor City. This can be seen from the p value obtained 0.00 and the maximum value obtained after counseling is 10 points.